Innocence et cruauté : approche anthropologique de la poétique d'Eugène Savitzkaya - Almeida, José Domingues de (2014)
One of the most impressive characteristics of the first novels (1977-1993) by the Belgian Minuit writer Eugène Savitzkaya, is about their specific modern pattern that some critics have called "hermetic". Many factors contribute to this feature: childhood remembrance; self-fiction; psychanalysis. Therefore, grammatical elements ensure characters, places and behaviours' ambiguity and undefinition. We will illustrate the narrative strategies in novels like Mentir, La disparition de maman or Les morts sentent bon; "novels" definitely based on ambiguity.